Peran Pendidikan Agama Islam dalam Penanganan Bullying di SMA 1926 Pamulang Tangerang Selatan - Ramadhani, Suci; Muslim, Ahmad Buchori (ISEDU : Islamic Education Journal, 2025)
The purpose of this study is to analyze and describe the implementation of Islam, describe bullying cases, and the role of Islamic religious education in preventing and handling bullying cases at SMA 1926 Pamulang South Tangerang. This research uses qualitative methods. The research was conducted at SMA 1926 Pamulang South Tangerang. The data sources in this study were the principal, PAI subject teacher, BK subject teacher and XI students. Data collection techniques are interviews, observation, documentation. Data analysis uses data collection, data reduction, data presentation, and conclusion drawing. Data validation uses credibility techniques including observation gap and triangulation. The results of the study show that the implementation of Islamic religious education in SMA 1926 was carried out in accordance with the independent curriculum that had been implemented. On the other hand, the bullying case that occurred at SMA 1926 Pamulang was relatively light. This means that bullying occurs in verbal forms such as slapping, calling friends by bad names, and other verbal forms. The role of PAI schools and teachers in preventing and overcoming bullying at SMA 1926 Pamulang is by providing anti-bullying education and socialisation, providing advice, holding religious programmes and providing punishment to the perpetrators of bullying.